Penerapan Nilai – Nilai Pancasila dalam Pembentukan Peraturan Hukum di Indonesia - Zainudin Hasan; Fathaniah Ghaisani Putri; Cinta Jivara Riani; Amanda Putri Evandra (Universitas Sains dan Teknologi Komputer, 2024)
As the Indonesian state philosophy, Pancasila plays an important role in forming the nation's moral and legal foundation. The application of Pancasila values is very important to realize justice, democracy and social welfare. All aspects of Indonesian national and state life are based on Pancasila in accordance with the five principles formulated by Moh. Yamin, Soepomo, and Soekarno. Pancasila, which is referred to as the state ideology, must remain strong in its position in all aspects. Pancasila is the highest source of state law in its position to form national law. As a source of state law, the value of each principle should be emphasized as a philosophical and sociological basis for every formation of Indonesian state legal provisions to create justice and protect legal provisions that might be carried out arbitrarily by the authorities. The Sequence of Legislative Regulations of the Republic of Indonesia recognizes Pancasila as the source of all sources of law. After reform, Law Number 10 of 2004, which was later changed to Law Number 12 of 2011, reaffirmed Pancasila.